Overview of the Knowledge Level and Behavior of Contact Lens Use among Medical Students of Universitas Kristen Krida Wacana - Pongtuluran, Regina; Mandalahi, Elisabeth Elida Elyus; Wangsa, Felix Jordan; Widyasa, Marni; Anugrahsari, Santi (Smart Medical Journal, 2023)
Introduction: Contact lenses are intended to treat refractive errors in the eye, as a diagnostic aid, and to support the personal appearance. A case study suggested that contact lenses cause eye diseases due to less knowledge and misbehavior when wearing contact lenses. This study was conducted to know the level of knowledge and behavior of using contact lenses among medical students of Universitas Kristen Krida Wacana (UKRIDA), intake 2016.Methods: It employed a descriptive analysis with a cross-sectional study. A total of 97 students who use contact lenses filled out a questionnaire in Google form.Results: The result demonstrated that 91 respondents (94%) had good knowledge about using contact lenses. Regarding behavior, 80 (93%) belonged to a good category.Conclusion: Their good knowledge and behavior towards using soft contact lenses might minimize their risk of red eye incidence upon using them.